Inter-fiber stresses in composites with carbon nanotube grafted and coated fibers. (19th June 2015) - Romanov, Valentin; Lomov, Stepan V.; Verpoest, Ignaas; Gorbatikh, Larissa
Abstract: Deposition of carbon nanotubes (CNT) on fiber surfaces is a promising technique to add functionalities to polymer composites. Upon deformation, these CNTs generate local stress heterogeneities which may affect properties of the interphase and the composite. The stress disturbance depends on the morphology of deposited CNT assemblies also linked to a deposition technique. In the present work, two types of morphologies are investigated: (1) CNTs grown on fibers; and (2) CNTs deposited in fiber coatings. The difference in the two cases is the orientation of CNTs near the fiber interface: radial for grown CNTs and tangent for CNTs in the coatings. Different parameters including CNT length, morphology of the grafting and density of the coating are evaluated. The analysis is performed using a recently developed two-scale model. Results show that CNT grafted and coated fibers produce distinctly different interface stresses.